Adoption of Rice Crop Manager - CGIAR Research Program on Rice (2018)
RCM is a decision-support tool designed for use by extension workers, crop advisors, agricultural service providers, and farmer leaders. It is accessible online on personal computers, tablets, or smartphones. In Philippines, more than 1.7 M recommendations generated for farmers in 2014-2018. In Odisha, India, around 100 thousand farmers have received recommendations in 2016-18.